Study of Japanese Experiences on Sustainable Urban Development including Pollution Control and Management, Resource/Energy Efficiency and GHG Reduction - World Bank (World Bank, Washington, DC, 2013)
In Japan, the sustainable development of cities and provinces has been vigorously pursued since the late 1990s under various programs through the initiative of the central government and local authorities. In 2009, the World Bank launched an urban development initiative called Eco2 Cities: Ecological Cities as Economic Cities (Eco2 Cities Initiative) to help cities in developing countries achieve greater synergistic ecological and economic sustainability. This study, entitled 'Study of Japanese Experiences on Sustainable Urban Development including Pollution Control and Management, Resource/Energy Efficiency and GHG Reduction,' was conducted to cover components A and C of the Eco2 East Asia Program with the following objectives: (i) To undertake a study of Japanese experiences on sustainable urban development including pollution control and management, resource/energy efficiency and GHG reduction (Task 1), and (ii) To coordinate and prepare the Eco2 international conference in Yokohama, Japan, on 21-23 October 2010 (Task 2). This report mainly focuses on Task 1, whose objectives are to compile and analyze Japanese experiences on sustainable urban development, including pollution control and management and resource/energy efficiency and GHG reduction, which are relevant to the Eco2 initiative and its implementation in cities in developing countries, as well as to draw lessons from these experiences for the implementation of the Eco2 initiative.